A Comparative Assessment of Various Turbulence Models Applied for Simulation of Air-Water Flow Over Chute Spillway - Shayanseresht, Saeed; Manafpour, Mohammad (Periodica Polytechnica Civil Engineering, 2021)
Chute aerators have been largely used to reduce cavitation hazard in high head spillways. There is no definite turbulence model for simulating these devices in smooth spillways in spite of its importance in critical conditions. A simulation in two-phase air-water chute flow and its aerator with five different turbulence models (RNG, Standard and Realizable k–ε Models, SST and Standards k–ω Models) has been numerically investigated by Fluent software. Finite Volume and VOF methods were used for discretization of flow equations and free surface modeling. Flow depth, velocity and bottom pressure comparison were made along with the air cavity length determination by numerical, experimental and reference equations. The best model with the minimum value of error percentage for flow depth and velocity was RNG k–ε turbulence model. The realizable and RNG k–ε turbulence models showed better results for the pressure head at the bottom of the chute. The RNG k–ε model results for the jet length have a very slight difference with the experimental results. The length of the cavity is closely associated with the flow emergence angle θ’ over aerators. The bottom air concentration of spillway chute simulated by all the turbulence models, except for the RNG k–ε model, can be overestimated and therefore may affect the designing of aerator geometry.